Eksplorasi Struktur Ilmu Pengetahuan (Konsep, Teori, dan Aplikasi) - Junaid bin Junaid; Ra'fah Jamilah Saadah; Yuzhril; Mariani (Jurnal Diskursus Islam, 2024)
The purpose of this research is to describe the structure of science. This type of research is qualitative by using conceptual analysis method. Data is obtained through library research by citing and analyzing relevant literature. The results showed that science is always juxtaposed and cannot be separated except in certain circumstances. As such, the structure of science is described as a description of the relationship between facts, concepts and generalizations that form the building of science. So that every time you analyze and prove a problem, you must always look at the background of the incident so that the proof of science can be considered a scientific statement. However, science is limited to things in accordance with human experience, because the function of human science is as a human tool in solving problems faced every day.